Analisis Pembelajaran IPA Materi Alam Semesta di Kelas VI SD Negeri 101866 Batang Kuis Pekan - Amelia Lestari Sinambela; Suyit Ratno; Nefo Puspita Lubis; Denny Hairunisia Putri; Roberto Jogi Rangga Sinaga; Trigita Sarumpaet; Ruben Situmeang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the teaching and learning process of Natural Sciences (IPA) on the topic of the universe in Class VI at SD Negeri 101866 Batang Kuis, Pekan. The study employs a qualitative descriptive method, utilizing data collection techniques such as observation, interviews, and documentation. The results show that the learning process adheres to the applicable curriculum, yet some abstract concepts in the universe material remain challenging for students to grasp. The teacher plays an active role in facilitating student understanding by employing a variety of teaching methods, including lectures, discussions, and demonstrations. However, the study reveals that these methods, while effective, may not fully engage students in the learning process. It is suggested that more innovative and student-centered strategies are necessary to foster greater student involvement and understanding. Additionally, the research indicates that the use of technology-based learning media could significantly enhance the students' learning experience by making abstract concepts more tangible. Furthermore, adopting a contextual learning approach, where students can connect the material to real-life situations, is recommended to increase student comprehension and retention. This study emphasizes the importance of adapting teaching methods to the evolving needs of students and integrating modern educational tools to make learning more interactive and meaningful. Ultimately, the study suggests that incorporating these strategies will improve the overall effectiveness of teaching Natural Sciences in elementary school classrooms.